The new railway tunnels of Frejus and Gothard: a political and institutional comparative analysis - Marletto, Gerardo (TeMA - Journal of Land Use, Mobility and Environment, 2011)
Projects of the two new railway transalpine tunnel of Frejus and Gothard have similar technical characteristics: an identical length (57 km), a similar cost (10 billion Euros) and the existence of a highway along the same Alpine corridor. But, whilst the new Gothard is now under construction and should become operational in 2017, the new Frejus is at standstill at preliminary phases and has faced a very strong local opposition on the Italian side of the Alps. This difference can be explained by analysing the political and institutional framework of the two projects. The new Swiss tunnel is integrated into a national scheme of transport policy which is based on: the development of a new system of railway infrastructures, which features two new transalpine tunnels (the new Gothard and the Loetschberg); the implementation of a distance-related heavy vehicle fee, which is levied on the basis of total weight, emission level and the kilometres driven; the provision of financial resources to stimulate the transfer of transalpine freight from road to railway. The approval of such a scheme started twenty years ago: it was based on a constitutional decree, implemented through several Federal acts and supported by three confirmatory referenda. The new French-Italian infrastructure is not integrated in any transport policy scheme. The new tunnel is only partially consistent with the overall goals of the European transport policy and the Transport Protocol of the Alpine Convention (which has not yet been ratified by the Italian Parliament): actually no action for modal shift is envisaged. Moreover, the new tunnel was initially supported by a structured consultative and participative procedure – based on the ‘débat public’ technique – only in France. In Italy this megaproject was not backed by an effective deliberation process, neither at the local nor the national level; on the contrary: it was considered among the strategic projects of the so-called ‘Legge obiettivo’ and therefore it could bypass the ordinary administrative procedures (and the otherwise mandatory environmental impact assessment). The late creation of a consultative committee (the so-called ‘Commissione Virano’) and the implementation of participative procedures have not been always consistent and has not proved valid to stop the fierce opposition to the project.